Heterostyly in Mussaenda I. dimorphism in floral characters of the pin and thrum morphs - Siar, S. V.; Rosario, T. L. (2001)
The phenomenon of heterostyly in Mussaenda was investigated. Based on the style and stamen lengths, the cultivars and species were classified as either pin or thrum type. The pin cultivars are 'Doña Eva', 'Doña Esperanza', 'Doña Hilaria', 'Maria Makiling', and 'Queen Sirikit'. The thrum cultivars are 'Mutya', 'Diwata', 'Doña Luz', 'Baby Aurora' (M. flava), and 'Doña Trining' (M. erythrophylla). Although its floral characters are not significantly different from those of the pin cultivars, 'Lakambini' is the only cultivar whose stamen and style are almost of the same length, a case of an intermediate type in Mussaenda reported for the first time. Dimorphism between the pin and thrum floral morphs is observed in terms of pollen size, pollen production, and in lengths of the anther, style, stigma lobes and papillae. Thrum morphs produced significantly more and bigger pollen grains but smaller and shorter stigma lobes and papillae than the pin morphs.
Keywords: Mussaenda (plant); Genetic polymorphisms